Efektivitas Media Pembelajaran Interaktif Baamboozle Terhadap Keaktifan Belajar Siswa Pada Materi Bilangan Cacah Kelas I MI - Anila uchtia Zulfa; Anista Ika Surachman (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
: This study aims to determine the effectiveness of the Baamboozle interactive learning medium on students’ engagement in learning about whole numbers in first grade. This study is an experimental study with a one-group pretest-posttest design. The research subjects consisted of 16 first-grade students at MI Terpadu Al Madani. Data collection was conducted using observation sheets to measure the level of student engagement during the learning process. Data analysis was conducted using descriptive statistics to determine the initial data profile, a Paired Sample t-test with the aid of IBM SPSS Statistics to test the difference between pretest and posttest scores, and an N-Gain test to determine the improvement in student engagement. The results of the study indicate a significant difference in student learning engagement between before and after the use of the Baamboozle interactive learning medium. This is demonstrated by the results of the Paired Sample t-test, which showed a calculated tvalue greater than the critical ttable (t0.05(14) = 2.145), specifically 22.376 > 2.145, and a significance level of 0.000 < 0.05. The posttest mean score of 17.00 is higher than the pretest mean of 10.31, and the N-Gain test results also show a mean of 0.69, which falls into the moderate category. Thus, the Baamboozle interactive learning media has been proven effective in increasing student engagement in learning about whole numbers.